Códigode barra de DNA como ferramenta na taxonomia de aves amazônicas - Bezerra, Elisama Franco (2013)
The DNA barcode has been successfully used in identifying the global avifauna with over 90% accuracy. Correct identification of species is important for the conservation of biodiversity and quantification. Thus this work aims to generate a database of sequences DNA barcode related vouchers deposited in the Collection of Birds from the National Institute for Amazonian Research (INPA) to confirm the reliability of BOLD (The Barcode of Life Data System ) in identifying the species of Amazonian birds with the current taxonomy. A sample was selected by species of Tissue Collection of the National Institute for Amazonian Research (INPA), totaling 422 samples from birds. The gene used as the DNA barcode is a mitochondrial cytochrome c oxidase gene 1 (COI). Validation of the gene COI barcode DNA as a tool for taxonomic identification of bird species in the Amazon, we had 72.9% of species identified correctly. Among the 407 species with DNA sequenced, 90 are unpublished sequences for BOLD. In 20 samples were indentificados taxonomic errors and only two samples identified the BOLD wrong. The DNA barcode interacts between the Classical and Molecular taxonomy for accurate identification of species. The results of this study demonstrate that taxonomic tool as the DNA barcode can be used for molecular identification of birds in the Amazon. Despite the lack of DNA sequences of Amazonian birds in the BOLD database, the species studied in this work showed 93.5% to 100% reliability, demonstrating the resolving power of this tool